2012
DOI: 10.1007/s00404-011-2196-z
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of local therapy with a vaginal lactic acid gel on dysuria and E.coli bacteriuria question our current views on recurrent cystitis

Abstract: Objective We tested the effect of vaginally applied lactic acid gel on symptoms and bacteriuria in acutely exacerbated recurrent Eschericia coli cystitis. Methods Carnoy fixed samples of the morning urine from 20 women with a history of recurrent E.coli cystitis were prospectively investigated for bacteriuria using fluorescence in situ hybridization (FISH). Results In 11/20 women with acute cystitis, the symptoms and bacteriuria were regressive with lactic acid gel treatment, without the need for antibiotic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…[30] Lactic acid was also shown to be a strong outer membrane disintegrating as well as permeabilising agent of gram-negative bacteria [31]. Swidsinski et al [16] have demonstrated a positive effect of a vaginal lactic acid gel on acute E. coli cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Lactic acid was also shown to be a strong outer membrane disintegrating as well as permeabilising agent of gram-negative bacteria [31]. Swidsinski et al [16] have demonstrated a positive effect of a vaginal lactic acid gel on acute E. coli cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…38 Esas bacterias producen ácido láctico a partir de la fermentación del glicógeno producido por las células epiteliales dependientes de estrógenos, manteniendo el pH ácido de la vagina, protegiendo la microbiota vaginal, previniendo las disbiosis y evitando la adherencia de uropatógenos incluido la E. coli que generan infección. [39][40][41] En contraste, las mujeres postmenopáusicas presentan cambios relacionados con la disminución de los niveles hormonales tanto de andrógenos como de estrógenos. Lo anterior resulta en atrofia del epitelio vaginal, llevando a la disminución en la concentración de Lactobacillus spp y a su vez, una menor producción de ácido láctico que aumenta el pH vaginal, lo que crea un ambiente más propicio para la sobreinfección del tejido urogenital.…”
Section: Patogénesisunclassified
“…P. Watnick и R. Kolter (2000) называют биопленки «городом микро-бов» [23]. Следует отметить, что увеличение ве-роятности формирования биопленки связано с увеличением количества условно-патогенных микроорганизмов в среде до 10 × 6 кое/мл [24].…”
Section: микробные биопленки: состав и разнообразиеunclassified
“…69 СТАТЬИ к клеткам вагинального эпителия в концентра-циях 10 × 5-6 [24]. При этом бактерии приоб-рели нитчатую «колониальную» форму, чему приписывается их резистентность к бета-лак-тамным антибиотикам.…”
Section: роль биопленок в формировании патологических процессов во влunclassified